2011
DOI: 10.22358/jafs/66164/2011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microalgae as sources of digestible nutrients for monogastric animals

Abstract: The study was carried out to evaluate three microalgae as potential nutrient sources in diets for monogastric animals. In a digestibility experiment with adult mink (Mustela vison), the microalgae Nannochloropsis oceanica, Phaeodactylum tricornutum and Isochrysis galbana were fed at 60, 120 and 240 g kg -1 as is, replacing fish meal. The N. oceanica and P. tricornutum had similar crude protein (CP) content (47.7 and 49.0% of DM, respectively), amino acid composition and lipid content (8.4 and 7.4%, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 25 publications
3
64
0
1
Order By: Relevance
“…lipid source. Skrede et al (2011) found decreased lipid digestibility with increased amounts of freeze-dried Nannochloropsis sp. included in diets for adult mink (Mustela vison), which was used as model organism due to the approved relationship with digestibility in salmonid fish and other monogastric species.…”
Section: Discussionmentioning
confidence: 90%
“…lipid source. Skrede et al (2011) found decreased lipid digestibility with increased amounts of freeze-dried Nannochloropsis sp. included in diets for adult mink (Mustela vison), which was used as model organism due to the approved relationship with digestibility in salmonid fish and other monogastric species.…”
Section: Discussionmentioning
confidence: 90%
“…In stark contrast, Skrede et al [50] used mink as a 261 'model' monogastric species for aquaculture and indirectly estimated the protein digestibility of a related 262 Nannochloropsis species (N. oceanica) to be very low (35%). To our knowledge, the only study to report 263 the in vitro protein digestibility of N. granulata algal biomass is that of Tibbetts et al [36] who found it to 264 be relatively high for whole-cell (84-85%) and lipid-extracted (88-91%) meals.…”
Section: Results 179mentioning
confidence: 99%
“…Unfortunately, the simple layout of the experiment does not help establishing to what extent the observed depression of lipid and gross energy ADC values is attributable to the inclusion of microalgae biomass in the diet. Comparisons with other studies are difficult since there have been very few investigations where the digestibility of dried microalgae biomass have been estimated in monogastric animals (Becker, 2007;Skrede et al, 2011) and even more so in fish, where the available information on this subject is particularly scarce. In the Arctic char and Atlantic salmon, Burr et al (2011) found the apparent digestibility of crude protein and gross energy of a sun-dried Spirulina sp.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the European sea bass (Tulli et al, 2012), a preparation including 16% by weight of a freezedried T. suecica biomass to replace fish trimmings of a control diet, resulted in still high but significantly lower ADC values of crude protein, lipid and organic matter. To our knowledge, the only study reporting estimates of the apparent digestibility of diets including a freeze-dried I. galbana biomass in a comparison with those of other marine microalgae such as Nannochloropsis oceanica and P. tricornutum was carried out by Skrede et al (2011) in mink as a carnivorous model for salmon. In that study, different to the present one, crude protein digestibility of diets including I. galbana and N. oceanica in graded levels (from 0 up to 24% dry weight) to replace same proportions of fish meal in a basal diet, was substantially reduced when just 6% of microalgae biomass was included in the diet whereas lipid apparent digestibility was adversely affected only at the highest level of substitution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation